Beyond leaf development: roles of the miR319/LANCEOLATE module in controlling tomato meristem size and flowering - Ferigolo, Leticia Frizzo (2022)
Flowering is one of the most important developmental stages in the plant life cycle. The proper flowering time, and the correct development of inflorescences and flowers are crucial for the reproductive success and vegetable crops yield. Many flowering characteristics are controlled by processes that occur in the shoot apical meristem, already in the vegetative phase. Processes ranging from the establishment of vegetative meristem size, its maturation, to the last stages of the development of floral whorls, determine the reproductive characteristics of a plant. MicroRNA-regulated transcription factors (miRNAs) play crucial roles in most of these steps. MiRNAs are responsible for the quantitative and spatiotemporal regulation of their targets, providing ideal expression patterns for organ development. Many pathways regulated by miRNAs have been described as essential in the regulation of leaf development, juvenile to adult transition, flowering time, and fruit ripening, among other developmental stages. TEOSINTE BRANCHED1/ CYCLOIDEA/ PROLIFERATING CELL NUCLEAR ANTIGEN FACTOR1 transcription factors (TCPs), several of which are regulated by miR319 (called CINCINNATA-like TCPs or CIN-TCPs), have a well-described and conserved role in leaf development. Among the CIN-TCPs, the role of the miR319/LANCEOLATE (LA) module in flowering seems to differ between Arabidopsis and tomato. Furthermore, the mechanism by which the miR319/LA module controls tomato flowering is not fully understood. Taking that into account, here we: (1) review the available literature on the main concepts of meristem maturation, transition to flowering, inflorescence development, and floral development, and (2) study how the miR319/CIN-TCP LA hub interconnects with different pathways in the regulation of meristem size and flowering. We show that the fine regulation provided by this hub controls vegetative meristem size, transition to flowering and flower development. The miR319/LA module acts by regulating the cell cycle and interacting with multiple phytohormone pathways, culminating in a fine-tuning of tomato reproductive development.